Comparison between modern western architettura and Islamic Arabic architecture“imitation and differences” - Bassam Abu Awwad, Dr. (International Journal of Engineering and Technology, 2019)
Architecture research is the mother of all art, representing the civilization of the population in every part; it is influenced by religion, politics and economy which are the foundations of its art over the centuries. Research on the architecture of Arab-Islamic civilization should be discussed primarily through generality principles of architecture, and the values granted and realized by the human sense of existing or loaded aesthetic qualities in the form of architecture, general. Then continue to look for the champions reached by the particular civilization. The position of the research in architecture, however, serves as a jump to conclusions before appropriate extracts are reached and not submitted to a rigorous examination. The research is a comparison between Arab-Islamic civilization and other civilizations that have created values for completeness. To facilitate this comparison, the research choose the civilization closest to Arab Islamic civilization in terms of the vision of existence and its proximity to the site, which is Western civilization. • Two civilizations have had so many shared values, thanks to the cultural and architectural imitations due to the proximity and commercial exchange between the East and the West, creating a mixed architecture, since the twelfth century. Christian civilization has made many moves, including multiple versions of completeness and various aesthetic values. While the Arab Islamic civilization reached an aesthetic value in its emergency phase, in the eighth century, and stopped in the twelfth century. Since the beginning of the nineteenth century, the Islamic Arab world has been aware of the entry of Napoleon into Egypt, since it addresses aesthetic values based on the knowledge of structural and aesthetic technology that has had no role in its creation:
Keywords: Arab-Islamic Civilization; Modern Western Architecture; Confrontation Imitation; Arabic Architecture.